Моби Дик, или Белый Кит: роман / Герман Мелвилл - Мелвилл Герман (Азбука-классика, 2007)
Экземпляры: АБ (20180608) / Инвентарный номер: 53419 / Цена: 123.42 / Сис.шифр: Ш6(7Сое) / Авт.знак: М 47 / ГРНТИ: 17.82.31 / ББК: Ш6(7Сое)